2021
DOI: 10.3390/molecules26154605
|View full text |Cite
|
Sign up to set email alerts
|

N-Skatyltryptamines—Dual 5-HT6R/D2R Ligands with Antipsychotic and Procognitive Potential

Abstract: A series of N-skatyltryptamines was synthesized and their affinities for serotonin and dopamine receptors were determined. Compounds exhibited activity toward 5-HT1A, 5-HT2A, 5-HT6, and D2 receptors. Substitution patterns resulting in affinity/activity switches were identified and studied using homology modeling. Chosen hits were screened to determine their metabolism, permeability, hepatotoxicity, and CYP inhibition. Several D2 receptor antagonists with additional 5-HT6R antagonist and agonist properties were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…This may lead to the malfunction of interneurons as manifested by cognitive, social dysfunction and behavioral disturbances through altered effects on a wide range of micro‐ and macro‐ systems [13,14] . More recent studies on the treatment of schizophrenia focus on the search for multitarget compounds with increased affinity for serotonin receptors and decreased or preserved affinity for the dopamine receptor [15–17] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may lead to the malfunction of interneurons as manifested by cognitive, social dysfunction and behavioral disturbances through altered effects on a wide range of micro‐ and macro‐ systems [13,14] . More recent studies on the treatment of schizophrenia focus on the search for multitarget compounds with increased affinity for serotonin receptors and decreased or preserved affinity for the dopamine receptor [15–17] …”
Section: Introductionmentioning
confidence: 99%
“…[13,14] More recent studies on the treatment of schizophrenia focus on the search for multitarget compounds with increased affinity for serotonin receptors and decreased or preserved affinity for the dopamine receptor. [15][16][17] In our previous studies we performed structure-based virtual screening [18] and identified, among others, virtual hit D2AAK1 [19] (see Figure 1) which displays nanomolar affinity to dopamine D 2 and D 3 as well as serotonin 5-HT 1A and 5-HT 2A receptors. Here we present the next step in our optimization campaign of D2AAK1 [20,21] From previously reported D2AAK1 derivatives, [21] we chose the most promising 3-(1-benzyl-1,2,3,6tetrahydropyridin-4-yl)-5-ethoxy-1H-indol (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the modifications introduced to the lead MST4 led also to promising multi-target structures acting on several targets simultaneously, e.g., three targets (5-HT 6 R, 5-HT 2A R and D 2 R, such as in compound 25 (K i = 78 nM vs. K i = 364 nM vs. K i = 149 nM, respectively)). Compounds acting on two such targets, i.e., 5-HT 6 R and D 2 R [ 31 ] or 5-HT 6 R and 5-HT 2A R [ 32 ], are described in the literature, but such three-target ligands are not yet available.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the above-mentioned 1,4-DACA, some specific fragments were used as primary pharmacophores, namely 7piperazinyl and 7-piperidinyl-3,4-dihydroquinazolin-2(1H)-one, 778 5-piperidinyl and 5-piperazinyl-1H-benzo[d]midazole-2(3H)-one, 779 4-(1-benzimidazolinone)piperidine, 780 sumanirole, 489,490,776,777 tranylcypromine, 472 pramipexole, 469 2phenylcyclopropylmethylamine, 527 eticlopride, 479,775 1,2,3,4-tetrahydro-3-quinolinamine, 776 tetracyclic, 781 tetrahydroisoquinoline, 480,498,594,595,600,[782][783][784][785][786][787] or 1,3-disubstituted morpholine. 438,474,490,493,788 Various aliphatic, 477,515,516,602,[789][790][791][792][793] bicyclic [794][795][796][797] or spirocyclic 798 amines have also been used for amine moiety. Generally, ligands with D 2 R selectivity were obtained using sumanirole 489,490,…”
Section: Primary Pharmacophorementioning
confidence: 99%